PENGARUH CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Kedathon, Dentamara; Utami, Endang Sri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
Financial reports from 2020-2022 on the IDX reveal diverse conditions in the food and beverage sub-sector. Several companies are facing profit decreases, with some not experiencing growth. The impact of the Covid-19 pandemic is a significant factor in these trends. Prolonged profit declines can lead to a decrease in company value. Additionally, ineffective corporate governance practices internally contribute to the deterioration of corporation value. This analysis intends to decide the impact of managerial ownership, institutional ownership, independent commissioners, and corporation size on corporation value. This analysis uses a population of all corporations in the food and beverage sub-company on the IDX term 2020-2022, a total of 31 corporations with a sample size of 17 corporations using the purposive sampling method to produce 51 observation data. This method of collecting analytical data is documentation that refers to the financial reports of food and beverage sub-sector corporations via the official IDX website. The results of the analysis state that managerial ownership, institutional ownership, and independent commissioners have a positive significant impact on corporation value. Meanwhile, company size does not affect corporation value.